Tripterygium Ingredients for Pathogenicity Cells in Rheumatoid Arthritis - Tang, Yujun; Liu, Qiuping; Feng, Yuxiang; Zhang, Yi; Xu, Zhenghao; Wen, Chengping; Zhang, Yun (Frontiers in Pharmacology, 2020)
Rheumatoid arthritis (RA) is an autoimmune disease mainly characterized by chronic polyarthritis. Many types of cells play pivotal roles in the pathogenicity of RA, such as T cells, B cells, macrophages, dendritic cells (DCs), osteoclasts (OCs), and fibroblast-like synoviocytes (FLS). Tripterygium wilfordii Hook f. (TwHf) and its ingredients are able to control disease activity by regulating the functions of cells mentioned above, and the clinical studies have highlighted the importance of TwHf ingredients in RA treatment. They have been demonstrated to improve the RA symptoms of animal models and patients. In this review, we discussed the effect of TwHf ingredients on pathogenicity cells, including disease/cell phenotypes and molecular mechanisms. Here, we constructed a cell-cell interaction network to visualize the effect of TwHf ingredients. We found that TwHf ingredients could inhibit the differentiation and proliferation of the pathogenicity cells. Besides, the components could decrease the levels of pathogenicity cytokines (i.e., interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α)). Many signaling pathways are involved in the underlying mechanisms, such as PI3K, NF-κB, and MAPK signaling pathways.